2010
DOI: 10.1007/s00213-010-1978-5
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of the antidepressant-like action of group II mGlu receptor antagonist, MGS0039

Abstract: RationaleSeveral studies have suggested that modulation of the glutamatergic system could be a new, efficient way to achieve antidepressant activity. Behavioral data showed that group II mGlu receptor antagonists (i.e., (1R, 2R, 3R, 5R, 6R)-2-amino-3-(3,4-dichlorobenzyloxy)-6-fluorobicyclo[3.1.0]hexane-2,6-dicarboxylic acid (MGS0039) and (2S)-2-amino-2-[(1S,2S)-2-carboxycycloprop-1-yl]-3-(xan th-9-yl) propanoic acid (LY341495)) elicited antidepressant activity in several animal models of depression in rats and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 42 publications
2
34
1
Order By: Relevance
“…To verify this hypothesis, we first investigated the involvement of the AMPA receptor in the mPFC in the antidepressant effects of the mGlu2/3 receptor antagonist and ketamine. We confirmed that the antidepressant effects of LY341495 and ketamine were abolished by pretreatment with systemic administration of an AMPA receptor antagonist, NBQX, in the present condition as previously reported (Koike et al, 2011a, b;Maeng et al, 2008;Pałucha-Poniewiera et al, 2010). Moreover, the antidepressant effects of LY341495 and ketamine were also blocked by microinjection of NBQX into the mPFC.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…To verify this hypothesis, we first investigated the involvement of the AMPA receptor in the mPFC in the antidepressant effects of the mGlu2/3 receptor antagonist and ketamine. We confirmed that the antidepressant effects of LY341495 and ketamine were abolished by pretreatment with systemic administration of an AMPA receptor antagonist, NBQX, in the present condition as previously reported (Koike et al, 2011a, b;Maeng et al, 2008;Pałucha-Poniewiera et al, 2010). Moreover, the antidepressant effects of LY341495 and ketamine were also blocked by microinjection of NBQX into the mPFC.…”
Section: Discussionsupporting
confidence: 93%
“…Of note, we have confirmed previously that the present treatment condition is sufficient for the pharmacological depletion of 5-HT in mice (Fukumoto et al, 2014). Contrary to our findings, it has been reported that the acute antidepressant effects of ketamine and an mGlu2/3 receptor antagonist in the FST and tail suspension test, respectively, were independent of the 5-HTergic systems (Gigliucci et al, 2013; Role of 5-HT in an mGlu2/3 antagonist and ketamine K Fukumoto et al Pałucha-Poniewiera et al, 2010). Although these differences may be ascribed to differences in the study paradigms or conditions among the studies, the precise reason remains unclear at present.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies demonstrate that mGlu2/3 antagonists, notably MGS0039 and LY341,495, have antidepressant actions in standard behavioural models [54,55]. In addition, the antidepressant actions of mGlu2/3 antagonists are blocked by pretreatment with an AMPA receptor antagonist, similar to the blockade of ketamine [54,56].…”
Section: Potential Synaptogenic Targetsmentioning
confidence: 96%
“…The involvement of other than mGlu 2/3 receptor subtypes in the action of LY341495 cannot be ruled out, either as the compound is a mixed antagonist of both group II and group III receptors. The mechanism of the antidepressantlike action of both compounds was shown to be independent on the serotonergic system; the drugs were still active after the depletion of serotonin, and their action was not antagonized by serotonergic receptor antagonists ritanserin or WAY100635 (Pałucha-Poniewiera et al, 2010b). However, the activity of the compounds was antagonized by NBQX, further supporting the role of the AMPA receptor in the antidepressant action of mGlu 2/3 receptor ligands Karasawa et al, 2006;Kawashima et al, 2005;PaluchaPoniewiera et al, 2010b).…”
Section: The Role Of Group II Mglu Receptors In the Mechanism Of Actimentioning
confidence: 69%